2021
DOI: 10.1108/oir-05-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the scientific literature's abstract writing style and citations

Abstract: PurposeThe citation counts are an important indicator of scholarly impact. The purpose of this paper is to explore the correlation between citations of scientific articles and writing styles of abstracts in papers and capture the characteristics of highly cited papers' abstracts.Design/methodology/approachThis research selected 10,000 highly cited papers and 10,000 zero-cited papers from the WOS (2008-2017) database. The Coh-Metrix 3.0 textual cohesion analysis tool was used to quantify the 108 language featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Prior research has predominantly relied on techniques such as string searches, sentiment analysis, and linguistic complexity analysis (e.g., Hassan et al, 2020;Sienkiewicz & Altmann, 2016). For example, Hu et al (2021) examined the association between citation counts of scientific articles and the writing styles of abstracts. Their analysis revealed that abstracts of highly cited papers had a more complex vocabulary, longer sentences, and more complex syntactic structures, and were less readable than uncited abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has predominantly relied on techniques such as string searches, sentiment analysis, and linguistic complexity analysis (e.g., Hassan et al, 2020;Sienkiewicz & Altmann, 2016). For example, Hu et al (2021) examined the association between citation counts of scientific articles and the writing styles of abstracts. Their analysis revealed that abstracts of highly cited papers had a more complex vocabulary, longer sentences, and more complex syntactic structures, and were less readable than uncited abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, for 10,000 highly cited and 10,000 uncited English language research articles published during 2008-2017 across 22 subject areas, abstracts of highly cited articles contained more complex, difficult, and professional terms. The highly cited articles also had more adjectives, adverbs, conjunctions, and personal pronouns and longer sentences, making them less readable compared with abstracts of uncited articles (Hu et al, 2021). For 71,628 abstracts from language and linguistics journals (1991 to 2020), abstract readability was low and decreasing over time, and the readability of abstracts negatively correlated with citation counts (Wang et al, 2022).…”
Section: Article Readability (Abstract or Full Text)mentioning
confidence: 99%